The European Neighbourhood Policy. Challenges for the Eastern Partnership: what's next? - Cristina JANDÎC; Maia PISANIUC (Eastern European Journal of Regional Studies)
The world we are living in changes day by day. To adapt better it is important to know what challenges exist. In this research paper I will focus my attention on the European Neighbourhood Policy of the European Union and more precisely on the Eastern Partnership in order to understand what were the reasons to create such a platform, what are the priorities and how it must change in order to ensure the spreading of the democratic values and European standards outside the EU borders. The methods used in this research paper are chronologically and progressive analysis.